Expanding spectrum, intrafamilial diversity, and therapeutic challenges from 15 patients with heterozygous CARD11-associated diseases: A single center experience - Urdinez, Luciano; Erra, Lorenzo; Palma, Alejandro M.; Mercogliano, María F.; Fernandez, Julieta Belén; Prieto, Emma; Goris, Verónica; Bernasconi, Andrea; Sanz, Marianela; Villa, Mariana; Bouso, Carolina; Caputi, Lucia; et al. (Frontiers in Immunology, 2022)
CARD11-associated diseases are monogenic inborn errors of immunity involving immunodeficiency, predisposition to malignancy and immune dysregulation such as lymphoproliferation, inflammation, atopic and autoimmune manifestations. Defects in CARD11 can present as mutations that confer a complete or a partial loss of function (LOF) or contrarily, a gain of function (GOF) of the affected gene product. We report clinical characteristics, immunophenotypes and genotypes of 15 patients from our center presenting with CARD11-associated diseases. Index cases are pediatric patients followed in our immunology division who had access to next generation sequencing studies. Variant significance was defined by functional analysis in cultured cells transfected with a wild type and/or with mutated hCARD11 constructs. Cytoplasmic aggregation of CARD11 products was evaluated by immunofluorescence. Nine index patients with 9 unique heterozygous CARD11 variants were identified. At the time of the identification, 7 variants previously unreported required functional validation. Altogether, four variants showing a LOF activity were considered as causative of CARD11-associated atopy with dominant interference of NF-kB signaling (CADINS). Additional four variants showed a GOF effect as well a spontaneous aggregation in the cytoplasm, leading to B cell expansion with NF-κB and T cell anergy (BENTA) diagnosis. The remaining variant exhibited a neutral functional assay excluding its carrier from further analysis. Family segregation studies expanded to 15 individuals the number of patients presenting CARD11-associated disease. A thorough clinical, immunophenotypical, and therapeutic management evaluation was performed on these patients (5 BENTA and 10 CADINS). A remarkable variability of disease expression was clearly noted among BENTA as well as in CADINS patients, even within multiplex families. Identification of novel CARD11 variants required functional studies to validate their pathogenic activity. In our cohort BENTA phenotype exhibited a more severe and expanded clinical spectrum than previously reported, e.g., severe hematological and extra hematological autoimmunity and 3 fatal outcomes. The growing number of patients with dysmorphic facial features strengthen the inclusion of extra-immune characteristics as part of the CADINS spectrum. CARD11-associated diseases represent a challenging group of disorders from the diagnostic and therapeutic standpoint, especially BENTA cases that can undergo a more severe progression than previously described.